Theories that underlie the prevalence of third molar impaction: New theory - Alhanouf Alkhuraiji (Saudi Dental Journal)
Introduction: The purpose of this review was to introduce a new theory being the mechanical theory which hypothesizes that modernization is related to a reduction in the functional activities of the jaw which in turn negatively impacted the structure of the jaw, mandibular teeth line. A secondary aim was to briefly review the evolution and growth theories. Based on the information that were reviewed, it was found that modern societies possess higher prevalence of temporomandibular joint dysfunction. Materials & methods: The proposed mechanical theory is an added value to explain the impact of modernization on the prevalence of impacted third molar. During this transition societal factors and peoples’ quality of life changes people’s eating behavior and the associated activities of the mastication apparatus, jaw activities. The aim of this review was to introduce a new theory being the mechanical theory which hypothesizes that modernization is related to a reduction in the functional activities of the jaw which in turn negatively impacted the structure of the jaw, mandibular teeth line. A secondary aim was to briefly review the evolution and growth theories. Conclusion: Based on the information that were reviewed, it was found that modern societies possess higher prevalence of temporomandibular joint dysfunction. The proposed mechanical theory is an added value to explain the impact of modernization on the prevalence of impacted third molar.